Thermal and Physical Properties of Patchouli Essential Oil Industry Residue as Renewable Feedstock for Bioenergy - Zainuddin Ginting; Adi Setiawan; Rizka Mulyawan; Wika Armadani; Yuda Hermawan; Ashish Shrestha (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
Patchouli plant is one of main agricultural commodities in Indonesia with an area of 64.67 ha. The solid waste produced from the distillation industry is around 98% of total feedstock. The aim of this research is to disclose the characteristics of solid waste biomass from patchouli essential oil industry harvested from Lhokseumawe, Indonesia. The properties of patchouli biomass before and after distillation was analyzed by using a number of techniques including proximate, bomb calorimeter, TGA-DTG, DSC and lignocellulosic analyses. Five kilograms of biomass was collected after patchouli harvesting then sorted into four categories i.e. leaves, branches and trunk. and mixture of all. Another set of biomass residue was collected after distillation process and grouped similar to those collected before distillation. All samples were then dried, ground and sieved to 50 mesh size. The analysis results showed that the highest heating value was observed from the sample of patchouli leaves collected before distillation process with a value of 15.65 MJ/kg where its volatile matter content was 81.26%. Compositional analysis of lignocellulosic suggested that 27% in pre-distilled branches. Mixture of all parts was found to contain 35% cellulose that was the highest. Lignin content with 42% value was found in after distilled trunk.